Organization Culture and its impact on Work Performance - Kamalakannan, Dr. R. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to assess direct and indirect influences of organization culture on work performance, as well as to evaluate the influences of each sub element of organization culture on work performance. The quantitative research has been chosen in order to meet the purpose of the research and to test those relationships empirically; the data is collected from structured questionnaire. Sample size is 230 and also Descriptive research study is used as a research design and followed simple random sampling method. The sample was selected from business process outsourcing (BPO) companies being operative in Chennai. These findings indicate a positive relationship between organization culture and work performance. Likewise, organization culture sub-elements, namely achieving Goals, empowerment, managing changes and teamwork were found positively impacting the work performance